2017
DOI: 10.7717/peerj.3379
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seroepidemiology ofHaemophilus parasuisin Sichuan province, China

Abstract: Haemophilus parasuis, the causative agent of Glässer’s disease, has been reported as widespread, but little is known about its epidemiology in the Sichuan province of China. The goal of our research is to reveal the prevalence and distribution of H. parasuis in this area. Sampling and isolation were performed across Sichuan; isolates were processed using serotyping multiplex PCR (serotyping-mPCR) and agar gel diffusion (AGD) for confirmation of serovar identity. This study was carried out from January 2014 to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The recent occurrence of outbreaks of Glässer's disease with serovar 7 strains of G. parasuis in Chinese and Brazilian swine herds (4,5) raise the question whether there has been an increase in virulence in strains of this serovar. This could potentially be explained by acquisition of virulence factors from more virulent strains by horizontal genetic exchange, which would readily be achieved by the efficient natural transformation system present in these species (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent occurrence of outbreaks of Glässer's disease with serovar 7 strains of G. parasuis in Chinese and Brazilian swine herds (4,5) raise the question whether there has been an increase in virulence in strains of this serovar. This could potentially be explained by acquisition of virulence factors from more virulent strains by horizontal genetic exchange, which would readily be achieved by the efficient natural transformation system present in these species (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study involving intranasal challenge of highly susceptible piglets confirmed the inability of this strain to cause infection (3). However, there have been recent outbreaks of GD with SV7 in swine herds in China (4) and Brazil (5). In Australia, nasal samples obtained from pigs showing clinical signs typical of GD were positive for SV7 G. parasuis (6).…”
Section: Introductionmentioning
confidence: 96%
“…Haemophilus parasuis, or Glaesserella parasuis (G. parasuis) according to the new taxonomic reclassification, is normally a benign swine commensal in upper respiratory tract but may cause severe vascular lesions and multiorgan dysfunction, eliciting serious economic losses annually worldwide [46,47]. Commercial bacterins are often used to vaccinate swine against H. parasuis, but the deficiency in crossreactivity makes sole-serotype inactivated vaccine an ineffective means of protection against this disease [48].…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction technique is a rapid and specific method for the molecular serotyping, and had been used for H. parasuis serotyping ( Jia et al, 2017 ; Lacouture et al, 2017 ; Wang et al, 2017 ). Accurate serotype identification is critical for epidemiological investigations or vaccine selection in H. parasuis infections.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is characterized by pneumonia, meningitis, arthritis, polyserositis, and septicemia. Outbreaks of Glässer’s disease have resulted in serious lethality and economic losses in the global swine industry ( Kim et al, 2002 ; Oliveira, Blackall & Pijoan, 2003 ; Palzer et al, 2015 ; Wang et al, 2017 ; Yu et al, 2012 ). There are 15 serovars of H. parasuis but also a large number of non-typeable (NT) isolates and these possess wide differences in virulence ( Kielstein & Rapp-Gabrielson, 1992 ).…”
Section: Introductionmentioning
confidence: 99%